Mosaics - Rabin, Michael 1936-.; Pommers, Leon. (S.l. Capitol P8506, 1959)
Contains works, original and arranged by Chopin, Wieniawski, Mompon, Scriabin, Debussy, Sarasate, Elgar, Engel, Ravel, Prokofiev, & Suk.
Program notes by James Lyons on slipcase.
Michael Rabin, violin; Leon Pommers, piano
Keywords: Violin & piano music; Violin & piano music, arranged